2021
DOI: 10.1111/iwj.13736
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of red cell distribution width as a prognostic criterion in severe burns

Abstract: This study was conducted to examine red cell distribution width (RDW) as a prognostic criterion in severe burns. The study is a descriptive correlational study and was carried out retrospectively. Patients with high RDW and low albumin values among severe burn injuries in the burn unit of a university hospital constituted half of the sample. Severe burns with RDW within normal range and a prognostic criterion for which albumin level normal and closest to normal accounted for the other half. RDW and albumin val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, studies have shown that the correlation of albumin and the lactic acid at admission as a correlate of complication rate, mortality, and length of stay in burn patients has been widely demonstrated. [29][30][31][32][33] As previously mentioned, the longer the duration of mechanical ventilation in burn patients, the higher the incidence of complications, the higher the mortality rate, and the longer the length of hospital stay. Therefore, there seems to be a specific correlation between albumin and lactic acid and prolonged mechanical ventilation, consistent with the present study's findings.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, studies have shown that the correlation of albumin and the lactic acid at admission as a correlate of complication rate, mortality, and length of stay in burn patients has been widely demonstrated. [29][30][31][32][33] As previously mentioned, the longer the duration of mechanical ventilation in burn patients, the higher the incidence of complications, the higher the mortality rate, and the longer the length of hospital stay. Therefore, there seems to be a specific correlation between albumin and lactic acid and prolonged mechanical ventilation, consistent with the present study's findings.…”
Section: Discussionmentioning
confidence: 92%
“…The treatment process of burn cases, which are mostly preventable injuries, requires the utmost attention and a multidisciplinary approach. 1,2 According to the World Health Organisation (WHO), the American Burn Association and the Centers for Disease Control and Prevention (CDC), 1.1 million people are injured due to burns every year, 3,4 and 3500 people die due to burn injuries. 5 Multiple organ failure is common in burn patients with progressively worsening prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…Burn injuries are one of the most common and extremely destructive health issues in human life 1 . Today, effective infection control, fluid resuscitation, nutritional supplements, and effective use of anabolic agents support healing of wounds in the preliminary period of burn injuries 2,3 . In addition, covering the burn surface with surgical grafting, multidisciplinary team approach, burn care, and rehabilitation practices are provided in burn treatment at an optimal level 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 Today, effective infection control, fluid resuscitation, nutritional supplements, and effective use of anabolic agents support healing of wounds in the preliminary period of burn injuries. 2 , 3 In addition, covering the burn surface with surgical grafting, multidisciplinary team approach, burn care, and rehabilitation practices are provided in burn treatment at an optimal level. 4 , 5 Quality of life and social support needs in burn patients came to the fore in the 1970seconds by Munster, 6 discussing the social limitations of burn trauma in human life for the first time.…”
Section: Introductionmentioning
confidence: 99%